2019
DOI: 10.3389/fpls.2019.00524
|View full text |Cite
|
Sign up to set email alerts
|

Robust Genetic Transformation System to Obtain Non-chimeric Transgenic Chickpea

Abstract: Chickpea transformation is an important component for the genetic improvement of this crop, achieved through modern biotechnological approaches. However, recalcitrant tissue cultures and occasional chimerism, encountered during transformation, hinder the efficient generation of transgenic chickpeas. Two key parameters, namely micro-injury and light emitting diode (LED)-based lighting were used to increase transformation efficiency. Early PCR confirmation of positive in vitro transgenic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 75 publications
0
27
0
Order By: Relevance
“…Chimeric tissue formation (a single plant tissue containing a mixture of transformed and non‐transformed sections) during tissue culture transformation is a prevalent issue in legumes, including cowpea (Das Bhowmik et al ., 2019). Chimeric plants affect the segregation of the transgene to the subsequent generation and reduce the efficiency of recovering stable transgenic lines (Das Bhowmik et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chimeric tissue formation (a single plant tissue containing a mixture of transformed and non‐transformed sections) during tissue culture transformation is a prevalent issue in legumes, including cowpea (Das Bhowmik et al ., 2019). Chimeric plants affect the segregation of the transgene to the subsequent generation and reduce the efficiency of recovering stable transgenic lines (Das Bhowmik et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Several selection systems have been reported for cowpea transformation with different explant types (Manman et al, 2013), such as NPTII/kanamycin (Bett et al, 2019; (a) (b) (c) The Plant Journal, (2021), 106, 817-830 Chaudhury et al, 2007), NPTII/G418 (Solleti et al, 2008b), PMI/mannose (Bakshi et al, 2012), HPT/hygromycin (Kumar et al, 1996), BAR/glufosinate (Popelka et al, 2006) and ahas/imazapyr (Citadin et al, 2013;Ivo et al, 2008). It was reported that incomplete selection and tissue necrosis were associated with those selection systems (Manman et al, 2013) and resulted in lower transgenic plant recovery (Bakshi et al, 2011;Chaudhury et al, 2007;Solleti et al, 2008b) and a higher percentage of chimeric tissue formation in cowpea (Das Bhowmik et al, 2019). To identify more efficient selection agents for the de novo organogenesis described above, we tested and compared the selection efficiency of CTP-NPTII/kanamycin, CTP-NPTII/G418 and CTP-spcN/SPEC (Anada et al, 2017) after Agrobacterium-mediated transformation using Agrobacterium strain LBA4404 Thy-.…”
Section: In Vitro Regeneration and Transgenic Selection Of Cowpeamentioning
confidence: 99%
“…The cultivar, DCP 92-3 responds well in plant tissue culture and exhibit limited performance under drought conditions, and hence, the cultivar was used in the present study. Transformation efficiency obtained in the current study is 0.1%, however the efficiency can significantly be increased by modulating parameters like micro-injury to explants and LED-based light simulations, as reported [35]. Transgenic chickpea lines harbouring AtDREB1a gene driven by stress inducible promoter rd29a were developed and tested for various physiological parameters crucial to drought adaptation.…”
Section: Discussionmentioning
confidence: 62%
“…The infection medium also contained AS and DTT and had an acidic pH, which are all factors that have been shown to facilitate T-DNA transfer and to enhance transformation efficiency (25). After 5 days of co-cultivation the moderate survival of explants was observed but with higher transformation efficiencies (26). In this study, DTT was added to the CCM as an antioxidant, to reduce pruning and necrosis in explants which represents one of the primary factors affecting the conversion efficiency (19).…”
Section: Analysis Of the Transgenic Plantsmentioning
confidence: 99%